Digital-Based Inclusion Education Strategy at Modern Islamic Boarding School - Sa'diyah, Halimatus; Zilfania Qathrun Nada; Winniyatul Hasanah (IAIN Madura, 2025)
Digital-based inclusive education has become a major focus in achieving the 2030 SDGs by various international organizations. Computer devices and the development of information and communication technology are currently very rapid. Most people have enjoyed this development, but there are still marginalized people such as children with disabilities, through adaptive technology, it is hoped that they can take part in learning like other normal children in an inclusive education setting. This research has an urgency to explain how the strategy of digital-based inclusion education at IBS Padepokan Kyai Mudrikah Kembang Kuning Pamekasan Madura Madura. This type of research is a case study with a qualitative approach. Data was taken from the interviews, observations and documentation which were then analyzed by means of data condensation, data display, conclusion drawing and data verification. The results of this study show that Digital based learning strategy in inclusive education held at IBS Padepokan Kyai Mudrikah Kembang Kuning Pamekasan Madura prioritizes mastery of technology in training the creativity of students. The use of technology in learning can help students with disabilities to to channel their ideas and skills in technology.